Conjugating the Present. Words inherited from Hannah Arendt and the public debate. Hannah Arendt: Thinking in company. November 30 – December 1, 2023, CCCB Barcelona. (Montserrat Espinosa) - Espinosa, Montserrat (HannahArendt.net, 2024)